Liability for Unlawful Acts Under the Business Judgment Rule and Piercing the Corporate Veil Doctrine - Isdiana Syafitri; Zulfi Chairi (Lex Publica, 2025)
The Board of Directors, as an organ of a limited liability company, holds full authority and responsibility in managing the company’s affairs. Nevertheless, in carrying out their duties, directors not infrequently commit unlawful acts that result in losses to the company as well as to third parties. This study aims to examine the concept of directors’ liability for losses suffered by a limited liability company caused by unlawful acts, the limits of such liability, and the available legal protection mechanisms. Employing a normative legal research method, this study finds that Law No. 40 of 2007 on Limited Liability Companies explicitly regulates the principles of fiduciary duty and the business judgment rule as the basis for evaluating directors’ liability. Directors may be held personally liable if it is proven that their actions constitute unlawful acts carried out in bad faith or due to negligence. The principle of piercing the corporate veil serves as a legal instrument that enables the disregard of the company’s separate legal personality in order to impose direct liability upon the directors.